Factors contributing to job satisfaction among employees of oil refineries in Pulau Indah - Hemavalli, Sandaramogam (2019)
Oil refineries nowadays always face challenges with absenteeism and turnover issue which is caused by job dissatisfaction. In order to increase their employee job satisfaction, employers are taking various measures. Organizations are focusing upon currently is analysing the factors contribute to employee job satisfaction and how to improve it. Employee job satisfaction is an area which is widely talked about and researched upon. However, the information gained on the matter is unique and subjective to the industry and country. Hence the main objective of this study is to investigate the factors contributing to job satisfaction among employees of oil refineries in Pulau Indah, Klang. There are four independent variables investigated which is working environment, participation in decision making, empowerment, reward and recognition. As for the dependent variable, it is employee job satisfaction. The data for the thesis is gained through a self-administered questionnaire from a sample size of 284 employees from two oil refineries based in Pulau Indah. Data which was gathered through questionnaires was analysed by using statistical package for social science (SPSS) software 20. Based on the data gained the correlation analysis results shows that all four independent variables are statistically significant but has only a small and moderate relationship. As for the regression analysis results the R2 gained is 26.7% which means only that much percentage has impact on employee job satisfaction using the mentioned variables. Moreover, the analysis also proves that out of four independent variables only three are significant which is working environment, participation in decision making, reward and recognition. Thus, from the research it can be concluded that management of oil refineries should focus more on these three variables while implementing their human resource policies. Besides these three variables, employers also should focus more on empowerment because it can help organizations to gain competitive advantage which will benefit them in the long run.